2012
DOI: 10.1039/c2dt31223a
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectroscopic and theoretical studies of the OTiF2, OZrF2 and OHfF2 molecules with terminal oxo ligands

Abstract: The isolated group 4 metal oxydifluoride molecules OMF(2) (M = Ti, Zr, Hf) with terminal oxo groups are produced specifically on the spontaneous reactions of metal atoms with OF(2) through annealing in solid argon. The product structures and vibrational spectra are characterized using matrix isolation infrared spectroscopy as well as B3LYP density functional and CCSD(T) frequency calculations. OTiF(2) is predicted to have a planar structure while both OZrF(2) and OHfF(2) possess pyramidal structures, all with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
70
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(89 citation statements)
references
References 101 publications
18
70
1
Order By: Relevance
“…3 can be ascribed to the shorter Ti-O 34 compared to Zr-O bonds. 35,36 The pore size distribution, obtained by a DFT fit to N 2 adsorption isotherms, shows two pore sizes at 6 Å and 9 Å, consistent with the tetrahedral and octahedral cages within UiO-66(Zr 100 ), respectively. 16 As Ti loading is increased, the tetrahedral cages remain unchanged, whereas the octahedral cages shrink by B1 Å and become increasingly broader in their distribution.…”
mentioning
confidence: 71%
“…3 can be ascribed to the shorter Ti-O 34 compared to Zr-O bonds. 35,36 The pore size distribution, obtained by a DFT fit to N 2 adsorption isotherms, shows two pore sizes at 6 Å and 9 Å, consistent with the tetrahedral and octahedral cages within UiO-66(Zr 100 ), respectively. 16 As Ti loading is increased, the tetrahedral cages remain unchanged, whereas the octahedral cages shrink by B1 Å and become increasingly broader in their distribution.…”
mentioning
confidence: 71%
“…UiO-66­(Zr 100 ) showed two pore sizes at 6 and 9 Å, which represented tetrahedral and octahedral cages. With the increase of the Ti­(IV) ion dopant, the pore size of octahedral cages was shunk by ∼1 Å, which was due to the shorter Ti–O than Zr–O bands. , At 1 bar and 273 K, the CO 2 uptake of UiO-66­(Ti 56 ) was 4.00 mmol/g, which was 1.8 times that of pure UiO-66. Molecular simulation showed that charge transferred from metal ions to ligands followed by a decrease of pore size, which enhanced the CO 2 adsorption enthalpy of frameworks .…”
Section: Methods For Controlling Surface and Pore Structure Of Mofsmentioning
confidence: 98%
“…If the compound composition corresponds to the formula (NH 4 ) 3 HfOF 5 , its vibrational spectra should contain the intensive band (both IR and Raman active) in the range 900 cm À1 , in accordance with the triple character (one + two ) of the Hf-O bond and a short distance of this bond (Gong et al, 2012). Similarly, the Ti-O bond has a triple character ( + 2) that ensures a rather short Ti-O distance in accordance with our structural determinations, and the Ti-O stretches appear at 870 and 897 cm À1 for (NH 4 ) 3 TiOF 5 and Rb 2 KTiOF 5 , respectively (Udovenko & Laptash, 2011).…”
Section: Figurementioning
confidence: 99%